Eupatilin regulates proliferation and cell cycle of cervical cancer by regulating hedgehog signalling pathway. (11th January 2020) - Wu, Zhao; Zou, Bingyu; Zhang, Xun; Peng, Xue
Abstract : Eupatilin (5, 7‐dihydroxy‐3′, 4′, 6‐trimethoxyflavone) is a natural active substance found in génépi group plants, and its pharmacological activities has been proven to be useful in the treatment of various cancers. However, whether eupatilin demonstrates anti‐cancer activity in cervical cancer is still under evaluation. To clarify this, cancer cell lines and nude mouse model were used in this study. The results indicated that eupatilin could inhibit the occurrence of cervical cancer both in vivo and in vitro. Cervical cancer cell lines (C4‐1, HeLa, Caski, and Siha) and Ect1/E6E7 cells were incubated with eupatilin (40μM) for 48 hours. Compared with the control group, the viability of cervical cancer cells decreased significantly, while the apoptotic cells increased significantly. Cell cycle analysis showed that eupatilin treatment of HeLa and Caski cells reduced the proliferation index. Eupatilin at 40 mg/kg also inhibited tumour growth in tumour‐bearing mice. Interestingly, weakened hedgehog signalling was observed in cervical cancer cells and tumours from tumour‐bearing mice after eupatilin treatment. Our results reveal the inhibitory effect of eupatilin on cervical cancer and shed new light on the molecular mechanism of its therapeutic effect. Significance of the study: Eupatilin inhibited proliferation via promoting apoptosis and cell cycle arrest in HeLa and Caski cervical cancer cell lines. In addition, nude mouse tumourigenicity assay proved that eupatilin can suppress tumour growth in vivo. Dramatically, these activities might be involved in hedgehog signal pathway.